PHRASEOLOGY RELATED TO BODY PARTS: A COMPARATIVE ANALYSIS OF ENGLISH AND UZBEK EXPRESSIONS - Kasimova Nafisa Farhadovna; Gafurjanova Ferangiz (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Phraseological units, particularly idioms involving body parts, constitute an integral part of both linguistic expression and cultural identity. They reflect how different societies conceptualize the human body, emotions, and behavior through figurative language. This article investigates English and Uzbek idioms with body-part components, analyzing their literal and figurative meanings, cultural connotations, translation challenges, and underlying conceptual metaphors. By comparing idioms across the two languages, the study identifies universal metaphorical patterns as well as culture-specific features, offering valuable insights for linguists, translators, and language learners.